Домашняя страница New • 6 * х + 5 *(х-2)=3х(х-2) ;

6 * х + 5 *(х-2)=3х(х-2) ;

 - 

6 * х + 5 *(х-2)=3х(х-2) ;

  • 6x+5x-10=3x^2-6x

    17x-3x^2

    x=5

  • 6 * х + 5 *(х-2)=3х(х-2)

    6x+5x-10=3x-6x

    3x-17x+10=0

    D=289-120=169

    x_1=frac{17+13}{6}=5

    x_1=frac{17-13}{6}=frac{2}{3}

    3*х+8*(х-5)=2х*(х-5)

    3x+8x-40=2x-10x

    2x-21x+40=0

    D=441-320=121

    x_1=frac{21+11}{4}=8

    x_1=frac{21-11}{4}=2,5


  • В New

    Автор:

    Оставить ответ

    Ваш адрес электронной почты не будет опубликован. Обязательные поля помечены*

    *

    *